PENYEBARAN BUDAYA ROBO-ROBO DARI KERAJAAN AMANTUBILLAH MEMPAWAH HINGGA MENJADI POTENSI WISATA DI KABUPATAN SINTANG - nurhana azizah; AureL Maynanda; Usman Radiana (Universitas PGRI Adi Buana Surabaya, 2023)
West Kalimantan is known as a multiethnic region with many ethnicities such as Dayak, Malay, Chinese, Bugis, Banjar, and Javanese. One cultural heritage that is still preserved by the Malay community of Sintang Regency is Robo-robo, which has cultural meaning and messages for teenagers. Robo-robo is a tradition of preventing problems and is important in maintaining good relations among family members during the month of Safar in the Islamic calendar. Cultural heritage such as Robo-robo not only serves as the identity of the region but also as a guide to life for the people. This research was conducted using library research methods, which involves collecting data through various activities related to data collection methods. Data collection techniques in library research can be done through documentation, such as finding data from records, books, papers, articles, or journals.